Absolute rate coefficients for photorecombination of beryllium-like and boron-like silicon ions. (17th March 2016) - Bernhardt, D; Becker, A; Brandau, C; Grieser, M; Hahn, M; Krantz, C; Lestinsky, M; Novotný, O; Repnow, R; Savin, D W; Spruck, K; Wolf, A; et al.
Abstract: We report measured rate coefficients for electron–ion recombination of Si 10+ forming Si 9+ and of Si 9+ forming Si 8+, respectively. The measurements were performed using the electron–ion merged-beams technique at a heavy-ion storage ring. Electron–ion collision energies ranged from 0 to 50 eV for Si 9+ and from 0 to 2000 eV for Si 10+, thus, extending previous measurements for Si 10+ (Orban et al 2010 Astrophys. J. 721 1603 ) to much higher energies. Experimentally derived rate coefficients for the recombination of Si 9+ and Si 10+ ions in a plasma are presented along with simple parameterizations. These rate coefficients are useful for the modeling of the charge balance of silicon in photoionized plasmas (Si 9+ and Si 10+ ) and in collisionally ionized plasmas (Si 10+ only). In the corresponding temperature ranges, the experimentally derived rate coefficients agree with the latest corresponding theoretical results within the experimental uncertainties.